2022
DOI: 10.3390/ijms23168947
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transposon-Derived Accessible Chromatin Regions in Rice (Oryza Sativa)

Abstract: Growing evidence indicates that transposons or transposable elements (TEs)-derived accessible chromatin regions (ACRs) play essential roles in multiple biological processes by interacting with trans-acting factors. However, the function of TE-derived ACRs in the regulation of gene expression in the rice genome has not been well characterized. In this study, we examined the chromatin dynamics in six types of rice tissues and found that ~8% of ACRs were derived from TEs and exhibited distinct levels of accessibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…LTR/Gypsy with distal HSs carried a higher number of chromatin states 12/13 and H3K9ac modification was increased significantly at distal HSs (Figure 6b,d), implying that these distal TEs may carry activated enhancer elements in the HSs. Further, the open signals on TEs in the proximal promoters were correlated with gene expression (Figure 6a), consistent with the gene expression induced by open promoters in rice [65]. Interestingly, our study revealed that genes with TE neighbors carrying HSs showed higher levels of expression compared with genes carrying TE neighbors without HSs (Figure 6a), indicating a positive significance of TE opening near genes.…”
Section: Discussionsupporting
confidence: 82%
“…LTR/Gypsy with distal HSs carried a higher number of chromatin states 12/13 and H3K9ac modification was increased significantly at distal HSs (Figure 6b,d), implying that these distal TEs may carry activated enhancer elements in the HSs. Further, the open signals on TEs in the proximal promoters were correlated with gene expression (Figure 6a), consistent with the gene expression induced by open promoters in rice [65]. Interestingly, our study revealed that genes with TE neighbors carrying HSs showed higher levels of expression compared with genes carrying TE neighbors without HSs (Figure 6a), indicating a positive significance of TE opening near genes.…”
Section: Discussionsupporting
confidence: 82%
“…Transposable elements (TE) are one of the driving forces of evolution, altering gene expression patterns [ 46 , 47 , 48 ], chromatin accessibility [ 45 , 49 , 50 ], and gene duplication and evolution [ 26 , 47 ]. It has been proposed that TEs may be the main driving force for genome evolution in several species, including Moso bamboo [ 51 ], Pinus tabuliformis [ 52 ], and Allium fistulosum [ 53 ].…”
Section: Discussionmentioning
confidence: 99%